The Believing Brain : From Spiritual Faiths to Political Convictions – How We Construct Beliefs and Reinforce Them as Truths /: From Spiritual Faiths to Political Convictions – How We Construct Beliefs and Reinforce Them as Truths. (2012) - Shermer, Michael
No abstract available